2001
DOI: 10.1046/j.1365-2141.2001.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Two new alleles of the RHCE gene in Black individuals: the RHce allele ceMO and the RHcE allele cEMI

Abstract: Summary. Six unrelated individuals of Afro-Caribbean origin, whose red cells have a marked reduction of the Rhe antigen expression, have been identified. All exhibited the same serological profile with anti-e monoclonal antibodies and lacked expression of the high frequency erelated antigen hr S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
(67 reference statements)
3
41
0
2
Order By: Relevance
“…We showed already that ceMO encoded a weak Rhe antigen 18 and bring evidence here that it may encode a partial Rhe antigen, as individual 11 produced anti-e and anti-ce antibodies. We showed previously that variants homozygous for ceMO or with a ceMO/cE genotype were typed RH:Ϫ19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed already that ceMO encoded a weak Rhe antigen 18 and bring evidence here that it may encode a partial Rhe antigen, as individual 11 produced anti-e and anti-ce antibodies. We showed previously that variants homozygous for ceMO or with a ceMO/cE genotype were typed RH:Ϫ19.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that variants homozygous for ceMO or with a ceMO/cE genotype were typed RH:Ϫ19. 18 Individual 11 is typed RH:19 because the associated R N allele encodes a polypeptide expressing RH19 (Table 3). Titers of antibodies were low, but we think that one should be cautious if transfusion occurs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rh system is extremely complex, not only in terms of molecular genetics but also because of the 54 antigens reported so far, some of them being of major clinical significance [10]. For years it has been demonstrated that some RHD variants, particularly those of the three African clusters [11], segregate with RHCE variants, which result in the expression of partial/rare antigens [12,13,14,15,16,17,18,19]. But it is currently unknown to what extent expression of various antigens carried by the CE allele is linked to the expression of variant D alleles.…”
Section: Introductionmentioning
confidence: 99%